(untitled) (Research, Society and Development, 2020)
One of the first problems to be treated in occlusal disorders is cross-sectional correction, which may involve a top bite, a single or bilateral. These atresias can often contribute to the aesthetic corrections of the smile including asymmetries of the face. Objective: Aiming at correcting facial asymmetries with rapid maxillary expansion supported by mini-screws, this work demonstrates a new technique through weakening and unilateral maxilla expansion that facilitates the return of the displaced mandible to the ipsilateral side of the expansion. Case report: With the use of holes made along the palate raphe , as already suggested in the literature, and also complemented in the region of the infra-zygomatic crest on the opposite side of the facial asymmetry, this favored the mandibular displacement towards the expansion side, thus correcting aesthetics of the face. Final Considerations: This approach to weakening the infra-zygomatic ridge with the intention of greater displacement of a hemi-maxilla to the opposite side to the facial deviation, may facilitate some non-surgical corrections of asymmetric individuals.